Phytochemical analysis, cytotoxicity and antioxidant activity of cuckoo pint (Arum maculatum) leaf extract - Al-Shmgani, Hanady SA; Kadri, Zahraa Hussein M; Al-Halbosiy, Mohammad MF; Dewir, Yaser Hassan (Acta Biologica Szegediensis, 2020)
Arum maculatum is traditionally used for the control of many diseases and illnesses such as kidney pain, liver injury, hemorrhoids. However, the detailed biomedical knowledge about this species is still lacking. This study reports on the bioactive components and the possible mechanisms underlying the antioxidant, anti-inflammatory and cytotoxic activity of A. maculatum leaf extract. Gas chromatography-mass spectrometry (GC-MS) was used for phytochemical analysis. Assay of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide ) (MTT) was used to determine the cytotoxicity in the murine cell line L20B upon exposure to different extract concentrations for 24 h. Enzyme-linked immunosorbent assay (ELISA) was used to detect pro-inflammatory cytokines and tumor necrosis factor-α (TNF-α). GC-MS analysis identified the presence of important phytochemical components, e.g., 9-octadecenoic acid, methyl ester, (E), hexadecanoic acid, methyl ester, followed by benzenepropanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-, methyl ester (17.74%), heptadecanoic acid, 16-methyl-, methyl ester and dibutyl phthalate. The results indicated a significant dose-dependent decrease in L20B cell growth at a dose of 400 μg/ml (IC50) that is associated with a significant 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. The results suggested that the aqueous extract of A. maculatum leaves have potent antioxidant activity and cytotoxicity against L20B cell line with potential pro-inflammatory activity.